Konsep Akinnah Al-qalb Wa ‘ilājuhā Menurut Al-quran Dalam Pembangunan Modal Insan - Jamaludin, Abdul Kamil (2021)
Human Capital Development Is A Continuous Effort That Determines The Survival Of A Civilization And Its Sustainability. Thus, The Human Development Desired Must Consider The Physical And Spiritual Aspects. Islam Views Qalb Is The Spiritual Component That Serves As The Fundamental Of The Process Of Becoming Human. One’s Triumph Over The Negative Elements In Enlivening And Purifying One’s Heart Results In The Development Of Good Personality, Happy Family, Harmonious Society And Competent Nation. Contrarily, A Hindered Human Qalb From Development Invites Chaos That Are Not Conducive To Peaceful Life. This Research Identified Quranic Verses Related To The Hindrance Of The Human Qalb And Its Treatment. Its Main Objective Was To Explore The Fundamental Concepts Of Human Capital Development As Viewed By Muslim Scholars. Additionally, This Study Examined The Concept Of Akinnah Al-qalb From Quranic Perspectives As Has Been Explained By Mufassirīn. Furthermore, The Study Also Investigated The ‘ilāj Akinnah Al-qalb Concept Through The Lens Of The Quran And Mufassirīn.